Virgin Coconut Oil-based Nanostructured Lipid Carrier Improves the Hypolipidemic Effect of Rosuvastatin - Shehata TM; Aldhubiab B; Elsewedy HS (International Journal of Nanomedicine, 2024)
Tamer M Shehata,1,2 Bandar Aldhubiab,1 Heba S Elsewedy3 1Department of Pharmaceutical Sciences, College of Clinical Pharmacy, King Faisal University, Alhofuf, Al-Ahsa, 36362, Saudi Arabia; 2Department of Pharmaceutics, Faculty of Pharmacy, Zagazig University, Zagazig, Egypt; 3Department of Pharmaceutical Sciences, College of Pharmacy, AlMaarefa University, Riyadh, 11597, Saudi ArabiaCorrespondence: Heba S Elsewedy; Tamer M Shehata, Email hsewedy@um.edu.sa; tshehata@kfu.edu.saBackground: Monitoring noncommunicable diseases is regarded as a critical concern that has to be managed in order to avoid a wide variety of complications such as increasing blood lipid levels known as dyslipidemia. Statin drugs, mostly, Rosuvastatin (RSV) was investigated for its effectiveness in treating dyslipidemia. However, reaching the most efficient treatment is essential and improving the effect of RSV is crucial. Therefore, a combination therapy was a good approach for achieving significant benefit. Although RSV is hydrophobic, which would affect its absorption and bioavailability following oral administration, overcoming this obstacle was important.Purpose: To that end, the purpose of the present investigation was to incorporate RSV into certain lipid-based nanocarriers, namely, nanostructured lipid carrier (NLC) prepared with virgin coconut oil (CCO).Methods: The optimized RSV-NLC formula was selected, characterized and examined for its in vitro, kinetic, and stability profiles. Eventually, the formula was investigated for its in vivo hypolipidemic action.Results: The optimized NLC formulation showed a suitable particle size (279.3± 5.03 nm) with PDI 0.237 and displayed good entrapment efficiency (75.6± 1.9%). Regarding in vitro release, it was efficiently prolonged for 24 h providing 93.7± 1.47%. The optimized formula was established to be stable after 3 months storage at two different conditions; 4°C and 25°C. Importantly, including CCO in the development of RSV-NLC could impressively enhance lowering total cholesterol level in obese rat models, which endorse the potential synergistic action between RSV and CCO.Conclusion: The study could elucidate the impact of developing NLC using CCO for improving RSV anti-hyperlipidemic activity.Keywords: Rosuvastatin, natural compounds, coconut oil, nanostructured lipid carrier, optimization, hypolipidemic activity